Social Legislation and Its Role in Enhancing Social Development - Altaany, Haitham M; Sakr, Ahmed Mohi Khalaf; Abdelbary, Osama; Abadel, Raba’a T (Journal of Ecohumanism, 2025)
Social legislation includes statutes and policies governing just about any aspect of the welfare and responsibility of individuals and groups in society and can include education, health, employment, and civil rights among others. This review aims at critically reviewing and synthesizing the literature on social legislation to advance social development: historical developments, theoretical conceptualizations, and empirical reviews of cross-national studies have been reviewed. Utilizing the systematic review approach, the present study searched for the publications across the database and had well-defined eligibility criteria. A relationship between strong/social legislation and measures of social welfare is shown; moreover, the importance of high-quality enforcement of the laws is demonstrated. Universal health care acts correlate a country or country’s people’s longevity and minimize health quality disparities. These freedom laws for education mean that compulsory schooling laws are positively related to the literacy levels of the population and raise mobility in the economy. Amendments to labor rights legislation for wages and the working environment improve employment satisfaction, bring down poverty rates, and contribute to economic security. Civil rights laws work against discrimination; reinforce the unity of the society, and encourage equality. However, challenges like insufficient funding, corruption, and cultural barriers affect the program implementation, most so in low and middle-income countries. Further suggestions include the enhancement of measures relating to enforcement, popularization of existing legislation, means’ financing, and legislation’s tailoring to regional specifics. When measured against such factors, social legislation can become a powerful lever towards social development and the building of a society based on justice.